2009
DOI: 10.1016/j.fertnstert.2009.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variations in serum estradiol concentrations on secretory endometrial development and function in experimentally induced cycles in normal women

Abstract: Eighteen normal women underwent pituitary down-regulation with leuprolide, followed by a 10-day treatment with 0.2 mg/d transdermal estradiol (E2) with subsequent allocation to one of two 10-day estradiol regimens plus 40 mg daily intramuscular P: supraphysiologic (0.2 mg/d transdermal E2 mg/d vaginal micronized E2) or subphysiologic (no exogenous E2 treatment). Average E2 and P in the supraphysiologic, physiologic, and subphysiologic groups were 1,175.9 pg/mL and 17.5 ng/mL, 136.9 pg/mL and 21.2 pg/mL, and 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Progesterone levels were similar in the two groups, 20.8 ng/mL vs. 18.3 ng/ mL. More recently, Groll et al (46) used GnRH agonist suppression of normally cycling women and used IM P administration in three groups of subjects: no supplemental E 2 , physiologic E 2 supplementation, and supraphysiologic E 2 supplementation. They studied the endometrium and also examined the expression of a number of putative biomarkers of endometrial function and found no difference between the three groups.…”
Section: Luteal Phase: Role Of Estrogenmentioning
confidence: 94%
“…Progesterone levels were similar in the two groups, 20.8 ng/mL vs. 18.3 ng/ mL. More recently, Groll et al (46) used GnRH agonist suppression of normally cycling women and used IM P administration in three groups of subjects: no supplemental E 2 , physiologic E 2 supplementation, and supraphysiologic E 2 supplementation. They studied the endometrium and also examined the expression of a number of putative biomarkers of endometrial function and found no difference between the three groups.…”
Section: Luteal Phase: Role Of Estrogenmentioning
confidence: 94%
“…In order to better understand these apparently conflicting data, this study group analysed gonadotrophin-releasing hormone downregulated cycles followed by oestrogen (at varying doses) and progesterone replacement (Groll et al 2009). Effects on endometrial histology and immunohistochemical staining for integrin subunit β, osteopontin, oestrogen receptor and progesterone receptors A and B were examined.…”
Section: Role Of Oestrogen In Embryo Implantationmentioning
confidence: 99%
“…Likewise, the human endometrium transiently expresses a receptive phenotype, lasting 2–4 days, during the mid-luteal phase of the cycle. However, this implantation window is not controlled by a nidatory E2 surge ( de Ziegler et al, 1992 ; Groll et al, 2009 ), perhaps reflecting that synchronized implantation of multiple human embryos is neither required nor desirable. Further, decidualization of the stromal compartment is not dependent on an implanting embryo but initiated during the mid-luteal phase of each cycle in response to elevated circulating progesterone levels and increased intracellular cAMP production ( Gellersen and Brosens, 2014 ).…”
Section: Introductionmentioning
confidence: 99%